2003
DOI: 10.1186/cc1882
|View full text |Cite
|
Sign up to set email alerts
|

Influence of passive leg elevation on the right ventricular function in anaesthetized coronary patients

Abstract: Correspondence: Massimo Bertolissi, bertolissi@rodax.net ∆p SSP/RVSP = pressure gradient between systolic systemic pressure and right ventricular systolic pressure; ∆p DSP/mRVDP = pressure gradient between diastolic systemic pressure and the mean right ventricular diastolic pressure (the mean value between diastolic and end diastolic right ventricular pressures); PLE = passive leg elevation; RVEDVI = right ventricular end diastolic volume index; RVED V/P = right ventricular end diastolic volume/pressure ratio;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…In contrast, PLR evoked an acute increase in SV with the increase withheld throughout the 10 min period simultaneously with a decrease in TPR. This is in agreement with studies in patients showing increased SV and CO within minutes (Bertolissi et al, 2003;Boulain et al, 2002;Paelinck et al, 2003;Schrijen et al, 1991), whereas CO tends to decrease from the first minute or remain similar to baseline when exceeding 5 min evaluation at an elevated SV (Boulain et al, 2002;Schrijen et al, 1991). Thus, SV seems to be sensitive to evaluate the changes in CBV.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, PLR evoked an acute increase in SV with the increase withheld throughout the 10 min period simultaneously with a decrease in TPR. This is in agreement with studies in patients showing increased SV and CO within minutes (Bertolissi et al, 2003;Boulain et al, 2002;Paelinck et al, 2003;Schrijen et al, 1991), whereas CO tends to decrease from the first minute or remain similar to baseline when exceeding 5 min evaluation at an elevated SV (Boulain et al, 2002;Schrijen et al, 1991). Thus, SV seems to be sensitive to evaluate the changes in CBV.…”
Section: Discussionsupporting
confidence: 91%
“…How stroke volume responds to PLR depends on the Frank-Starling mechanism, including cardiac contractility and preload [ 3 ]. Bertolissi et al further confirmed that cardiac index is unchanged during PLR in those with reduced right ventricular ejection fraction [ 9 ]. Moreover, PLR may also identify impairment of diastolic functional reserve during exercise in patients with abnormal myocardial relaxation [ 10 ].…”
Section: Introductionmentioning
confidence: 96%
“…The head-down position was reported to be effective in the management of post-induction hypotension during cardiac surgery [19]. On the other hand, some reports showed that neither the leg-elevation position [20] nor the head-down position [21] improved the hemodynamic profile in cardiac surgery patients. No studies to the best of our knowledge had evaluated the hemodynamic effects of the two study positions in non-cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%